SISTEM PENGGAJIAN TERHADAP PENGENDALIAN INTERN DI RUMAH SAKIT PANTI NIRMALA MALANG - Putri, Ayu Kemala; Hendrawaty, Rina (Manajemen & Bisnis Jurnal, 2019)
Accurate information is a major requirement for management in carrying out all activities related to achieving the stated goals. This information has an important role in the process of controlling and making decisions on the company's operations that have been and will be carried out, so that it can be said that the success of management depends on the information and whether information is owned accurately. Internal payroll system for good payroll is expected later ease the burden of payroll, so that it can be used as a monitoring tool for the company. Therefore, in a company there needs to be an adequate payroll system and procedure which includes recording time attendance, recording working time, making payroll, making procedures for proof of cash out, salary distribution procedures and procedures for payment of wages in which the implementation is an internal control. The results of the study explained that payroll accounting systems, payroll systems, payroll procedures and organizational structure simultaneously affect internal control of the Pirm Nirmala Hospital and partially each payroll accounting system, payroll system, payroll procedure, and organizational structure also very influential for control intern of Panti Nirmala Hospital Malang. Keywords: Payroll accounting system, Payroll system, Payroll procedure Organizational structure and Internal control